Enhancing climate smart agriculture access and adoption: 1,100+ farmers trained in Makindu sub-county, Kenya. - Ogutu, Liz; Nderi, Alex Nduah; Nzuki, Esther; Waswa, Boaz (2025)
Over 1,100 farmers in Makindu Sub-County have benefited from AICCRA and Kimatwa Women SACCO’s climate-smart agriculture (CSA) initiatives. The partnership co-developed solutions to boost resilience, including experiential learning, a revolving seed scheme, and "Rip 1, Get One Free" tractor ripping services. CSA adoption rose by 30%, with 30 farmers becoming trainers. For the first time in seven years, farmers saw stable bean yields and improved harvests of maize, green grams, and cowpeas in 2023-2024, increasing food security and climate resilience.